The Cliff Effect Following the OJK Restructuring on the Credit Quality of ABC Rural Bank - Audita Salsabila Nasution; Widya Perwitasari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyze the cliff effect phenomenon on the asset quality of Rural Banks (BPR) following the termination of the Financial Services Authority's (OJK) credit restructuring policy. Employing a descriptive quantitative approach, this study utilizes year-on-year trend, comparative, and pre-post policy analyses to identify structural changes in the Non-Performing Loan (NPL) ratio through discontinuity analysis before and after the revocation of POJK No. 11/POJK.03/2020 in March 2024. The data utilized consist of the published financial statements of BPR ABC for the 2020–2024 period. The results indicate a structural discontinuity across three phases. The average NPL during the full relaxation phase (2020–2022) at 5.67% spiked in two waves, reaching 9.79% in 2023 and 15.47% in 2024. This total increase of 9.80 percentage points indicates a cliff effect. These findings demonstrate that countercyclical policies can create distortions in risk signals, potentially misleading decision-making processes. This study provides significant implications for regulators and bank management in designing more adaptive risk mitigation policies.